Beef Cattle Development Strategy Based on Agricultural By-Products in Lebong Regency Bengkulu - Ramon, Erpan; Nurhaita, Nurhaita; Firison, Jhon; Hidayat, Taufik; Ishak, Andi; Efendi, Zul; Rosbarnawan, Ferdy; Tresia, Gresy Eva; Puastuti, Wisri; Sutedi, Endang; Kusumaningrum, Diana Andrianita; Harmini, Harmini; Rahman, Taupik; Yulistiani, Dwi (Jurnal Agripet, 2025)
Lebong Regency is one of the areas in Bengkulu with very low beef cattle population covering only 0.189% of the total 161,000 heads. Although ongoing government and stakeholder initiatives have aimed to boost smallholder populations, the outcomes remain suboptimal. This study aimed to evaluate the potential and formulate strategies to increase the beef cattle population in Lebong Regency. It used a descriptive approach through surveys and interviews involving 40 participants, including 32 smallholder farmers and 8 experts from institutions supporting livestock development in the region. Secondary data from Statistics Indonesia supported the assessment of potential and challenges. Data were analyzed using a SWOT matrix, revealing the potential carrying capacity of 10,319 cattle heads, indicating an opportunity for livestock growth in Lebong Regency. The SWOT analysis positioned the strategy in quadrant III (0.33; -0.19), suggesting a turnaround approach. The recommended development strategy emphasizes enhancing knowledge of integrated technology through collaboration between coffee processing industry owners and rice/corn farmers producing agricultural waste. Additionally, utilizing government programs to increase knowledge, scaling up beef cattle farming, and strengthening institutional cohesion are key strategic actions.